Laboratorio de Biotecnología. Centro Interdisciplinario de Investigación para el Desarrollo Integral Regional, Instituto Politécnico Nacional, Unidad Durango. Becaria COFAA; Sigma 119, Fraccionamiento 20 de Noviembre II, Durango, Dgo., 34220, México - Shahid Aziz,; Hidayat Hussain,; Anisa Younis,; Habib ur-Rehman,; Muhammad Shahid,; Arshad Farooq Butt,; Ivan R Green, (International Journal of Phytomedicine, 2017)
Phytochemical and biological investigations were undertaken on ethanolic extracts of the leaves and root bark of Justica adhatoda L. Alkaloids, cardiac glycosides, tannins, steroids and saponins were detected in extracts from both parts of the title plant. Reducing sugars were not detected in either extract whereas flavonoids were detected in ethanolic extract of J. adhatota leaves only. Significant antibacterial and antifungal activities against Escherichia coli, Staphylococcus aureus and Aspergillus niger were demonstrated by both the leaf and root bark extracts. Additionally, both extracts displayed good antioxidant and heomolytic potential. Interestingly, eight metal ions were detected in both extracts in different concentrations.